Rhizome cinema-sexuality: a training experiencie on porpuse of art, esthetic and biology (2016)
This paper tackles relationship between cinema-sexuality from the challenge thinking that put in circulation the rhizome concept, which is configured like possibility of mapping a map in relation with question about ways we are constituted like individual of the sexuality, but also of the connections in multiplicity are liable of putting together and unravel when unexpected manner it provokes interruptions with we coming being about of thinking sexuality as a training experience. In this sense, rhizome cinema-sexuality refers to some connections and interruptions about art, esthetic, and biology, we are invited to relocate the relevant way of looking exposed to the education for sexuality like one of the contract responsibilities. So as to, sexuality is made visible as a training experience concerning some proposals have been made in Biology Department,specifically, from research line Trayectos y Aconteceres, which are connected with pedagogical relationship between teacher and student, school, as space of mobilization and training, and of course, an issue as teachers are called: Biology. From, it is trying to put in discussion question about legalize looking about established things, and also, possibilities of opening experience of individuals.